DNase I-hypersensitive sites associated with expression and hormonal regulation of mouse C4 and Slp genes. - Hemenway, C (1987)
There are four major regions of DNase I hypersensitivity in the 5' regions of the genes for the murine fourth component of complement (C4) and its homologous neighbor, Slp (sex-limited protein). Hypersensitivity around the start site of transcription and approximately equal to 0.5 kilobases upstream correlates qualitatively with expression of these genes. Two hypersensitive sites, at -2.3 and -2.0 kilobases, map specifically to the Slp gene and correlate with its hormonal regulation. That is, these sites are more prominent in male liver chromatin and become more apparent in chromatin from females treated with testosterone. Further, these sites are established in males to a greater extent than in females prior to expression of Slp and may reflect gene-commitment events. Comparison of chromatin from mouse strains differing in C4 and Slp alleles indicates that the four regions of hypersensitivity may be necessary but are not sufficient for high levels of expression.